2019
DOI: 10.1007/s00421-019-04256-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mountain ultra-marathon running on plasma angiopoietin-like protein 4 and lipid profile in healthy trained men

Abstract: Purpose Angiopoietin-like protein 4 (ANGPTL4) regulates lipid metabolism by inhibiting lipoprotein lipase activity and stimulating lipolysis in adipose tissue. The aim of this study was to find out whether the mountain ultra-marathon running influences plasma ANGPTL4 and whether it is related to plasma lipid changes. Methods Ten healthy men (age 31 ± 1.1 years) completed a 100-km ultra-marathon running. Plasma ANGPTL4, free fatty acids (FFA), triacylglycerols (TG), glycerol (Gly), total cholesterol (TC), low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Furthermore, significant positive correlations were found between exercise-induced increases in plasma ANGPL4 and those of plasma IL-6, TNF-α, FFA and Gly. The positive relationship between exercise-induced changes in plasma ANGPTL4 and those of plasma FFA shown in this study confirmed the data obtained in our previous investigation performed in healthy young men during a mountain ultra-marathon run 40 . We argued then that the elevated level of ANGPTL4 increased plasma FFA and the raised FFA would boost the release of ANGPTL4.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, significant positive correlations were found between exercise-induced increases in plasma ANGPL4 and those of plasma IL-6, TNF-α, FFA and Gly. The positive relationship between exercise-induced changes in plasma ANGPTL4 and those of plasma FFA shown in this study confirmed the data obtained in our previous investigation performed in healthy young men during a mountain ultra-marathon run 40 . We argued then that the elevated level of ANGPTL4 increased plasma FFA and the raised FFA would boost the release of ANGPTL4.…”
Section: Discussionsupporting
confidence: 92%
“…Whole-blood samples were used to measure lactate (LA) concentration and the hematocrit. The 90-min recovery period was selected based on the data from the available literature 39 , 40 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant changes in body composition parameters and metabolic/muscle damage-related blood markers have been repeatedly reported after endurance and ultra-endurance races. 3,[13][14][15][16]18,21,26,33,[40][41][42][48][49][50][51][52][53][54] These changes are closely related to race distance 50 and race pace reduction, at least in marathon and ultra-marathon young runners. 48,55 The results of this study indicate, for the first time, that in a given trail length, the time needed to complete a mountain trail race, which is determined also by the race pace, is closely associated with race-induced changes in body composition and metabolic/muscle damage-related blood markers in recreational master mountain runners.…”
Section: Discussionmentioning
confidence: 99%
“…The native full-length protein (FLANGPLT4), composed of 406 amino acids, is proteolytically cleaved into two fragments, a N-terminal coiled-coil domain (nANGPTL4) encompassing amino-acid 1 to 170, and an ANG/fibrinogen-like C-terminal domain (cANGPTL4) encompassing amino-acid 171 to 406 (Supplementary Figure 1). This proteolytic cleavage of FLANGPTL4 at the -RRXR-cleavage site by proprotein convertases depends on the tissue in which ANGPTL4 is synthesized and on the physiological or pathological circumstances [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%